Impact of early decompression surgery and injury characteristics on neurological recovery following traumatic cervical spinal cord injury - Ngo Dinh Trung; Hoang Xuan Su; Dao Trong Chinh; Nguyen Chi Tam; Le Nam Khanh; Do Van Nam (Brain and Spine)
Introduction: Traumatic cervical spinal cord injury (SCI) frequently leads to severe neurological deficits. Early decompressive surgery, when performed shortly after the injury, is believed to improve outcomes. However, the impact of surgical timing, calculated from the moment of injury, and injury characteristics on neurological recovery remains poorly understood. Research question: This study aims to assess the impact of early decompressive surgery and injury characteristics on neurological recovery in traumatic cervical SCI patients. Material and methods: A retrospective case-control study was conducted at the 108 Central Military Hospital in Hanoi, Vietnam, between January 2018 and June 2023. Data collected included demographics, injury characteristics, time from injury to decompression surgery, and clinical outcomes at the 1-year follow-up. Results: Among the 193 patients initially screened, 156 met the inclusion criteria. Neurological recovery was observed in 44.2 % of patients. Early decompression within 24 h significantly improved recovery outcomes (OR = 3.12, p = 0.006). Injury at C1–C3 levels, longer spinal cord injury length, and severe spinal canal stenosis were associated with poorer recovery (OR = 0.34, p = 0.015; OR = 0.21, p < 0.001; OR = 0.34, p = 0.009, respectively). Prolonged ICU stay correlated with worse recovery (OR = 0.90, p = 0.002). Discussion and conclusion: Early decompressive surgery, thorough assessment of injury characteristics, and minimizing ICU stay duration are critical for improving neurological recovery. These findings highlight the importance of timely surgery and strategic clinical management in enhancing recovery outcomes in traumatic cervical SCI patients.